Risk and reward in asset management delivery who is best prepared for the challenges ahead? : delegate information, 14 November 2003 : a water environment conference (Thomas Telford, 2003)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a conference held on 14 November 2003.